Exact algorithms for size constrained clustering - Jianyi Lin (Mathematical Sciences, 2013)
Clustering or cluster analysis [5] is a method in unsupervised learning and one of the most used techniques in statistical data analysis. Clustering has a wide range of applications in many areas like pattern recognition, medical diagnostics, datamining, biology, market research and image analysis among others. A cluster is a set of data points that in some sense are similar to each other, and clustering is a process of partitioning a data set into disjoint clusters. In distance clustering, the similarity among data points is obtained by means of a distance function.